THE EFFECT OF TEACHER’S FEEDBACK ON STUDENTS’ WRITING ACHIEVEMENT - Fitriana Fitriana (Faculty of Teacher Training and Education, Universitas Sriwijaya, 2017)
Abstract: The objectives of this study were to find out whether or not there were significant improvements in students’ writing achievement after they were taught by using feedback and significant difference between the students who were given feedback and that of those who were not. Investigating the students’ perception about teachers’ feedback was also the aim of this study. Applying the quasi-experimental research design, this study got involved 94 eighth graders of SMPN 3 Banyuasin 1 in the academic year of 2013/2014 as the population and the sample was 40 students who were selected based on their English proficiency test. The data for this study were collected by using a writing test and analyzed by using t-test and percentage analyses. The finding showed there was a significant improvement in the students’ writing achievement after they were received teachers’ feedback. There was also a significant difference between the students who were given feedback and that of those who were not. The finding also showed that teacher’s feedback was perceived very helpful by the students. To conclude, this study showed that teacher’s feedback played a very important role in helping students improved their writing performance. Key words: teacher’s feedback, writing achievement, students’ perception on teacher’s feedback